Policy brief: Optimising antimicrobial usage in paediatric inpatient hospital settings - J Cloete; M Karsas; T Chetty; A Pillay; M Archary; D Moore; T Reddy; Y Balakrishna; F Nakwa; R Lancaster; A Goga; P Jeena (South African Medical Journal)
Antimicrobial resistance (AMR) poses a global threat, partly fueled by antimicrobial overuse. Paediatric inpatients are particularly vulnerable to infections, leading to high antimicrobial consumption. In low-to-middle income countries (LMICs) like South Africa, research on antimicrobial usage for neonatal and paediatric healthcare-associated infections (HAI) is limited. This cross-sectional study evaluated antimicrobial usage in three academic public sector hospitals in South Africa to improve appropriateness. 22.9% of hospitalised children received at least one prescribed antimicrobial, with neonates, infants, and adolescents having higher prescription rates for HAIs. Common antimicrobials prescribed included beta-lactamase sensitive penicillin, aminoglycosides, and carbapenems. Antimicrobial selection aligned with the WHO AWaRe classification system. HIV infection did not emerge as a risk factor for HAIs or excessive antimicrobial usage. The policy brief recommends several strategies, summarized by the acronym 'PRACTICE,' to optimize antimicrobial prescribing practices. These include implementing standardized policies for empiric antimicrobial use, routine review of antimicrobial therapy, age-specific antimicrobial stewardship programs, and continued collaborative efforts and research. Individualized treatment plans, improved infection prevention and control measures, ongoing surveillance, and exploring electronic technology for antimicrobial stewardship are also crucial. Addressing antimicrobial usage is imperative to combat the growing threat of AMR and improve patient outcomes in LMICs like South Africa.